Evidence of ovine brucellosis due to Brucella ovis and Brucella melitensis in Karnataka, India - SHOME, R; SAHAY, S; TRIVENI, K; KRITHIGA, N; SHOME, B R; RAHMAN, H (The Indian Journal of Animal Sciences, 2018)
Ovine brucellosis is often neglected contagious bacterial disease causing enormous economic losses to sheep industry. India is recognized as geographical hotspot for brucellosis and there is only one seroprevalence report of Brucella ovis infection in sheep. Ovine brucellosis is caused by both rough and smooth strains of Brucella sp. In the present study, 300 sheep serum samples collected from 9 different districts of Karnataka by 3 stage random sampling approach were screened by antibody and DNA detection tests (RBPT and iELISA) and PCR. Antibodies specific to B. melitensis and B. ovis infection were 8.67% and 5.34%, respectively. In the same set of samples, 5% (15/300) showed Brucella DNA amplification by bcsp31 and IS711 genus specific PCRs. In B. melitensis and B. ovis species specific PCRs, 3.34% and 1.67%, respectively were detected positive indicating presence of both Brucella species in sheep population. Among the 7 districts, Yadgir, Tumkur, Raichur and Bagalkot showed higher prevalence of antibodies against rough and smooth strains of Brucella. This emphasizes the need for sensitization of national system in designing surveillance and control strategies for both B. ovis and B. melitensis infections in sheep.